PENGARUH MODEL PEMBELAJARAN PICTURE AND PICTURE TERHADAP HASIL BELAJAR GEOGRAFI - Siti Fadjarajani; Ely Satiyasih Rosali; Widyanti Noerdianasari (Perspektif Ilmu Pendidikan, 2020)
This research was conducted in social studies class X of a state high school in Ciamis Regency with the aim to determine the effect of using the type of picture and picture cooperative learning model on the improvement of student learning outcomes. The method used is quasi-experimental model with a pre-test post-test control group design. Data analysis was performed by calculating the value of t. The results showed that the use of the cooperative learning model type picture and picture gave a significant effect in learning outcomes of students' cognitive domains (tcount > ttable). It is necessary to use varied learning models so that students will be more active and have better acceptance of the material presented so that it contributes to improving learning outcomes and the achievement of the specified KKM.